Biobehavioral Management of Headaches - Nogueira, André Marinho Paiva; Santos, Gabriela Cacau Sousa; Vieira, Luis Eduardo Matoso; Nogueira, Déborah Marinho Paiva; Lima, Raynrich Kevin Assis; Santos, Isabela Cacau Sousa; Lima, Gabriel Coelho Gondim de Oliveira (Headache Medicine, 2023)
Full abstract in PDF.